Improving ototoxicity monitoring in patients receiving aminoglycosides using a novel digital approach: a quality improvement project - Andrew Jones; Francis Drobniewski; Michael Loebinger; Emily Frost; Julie Wilkins; Presanna Premachandra; Anand Shah; Su Madge; Nicholas J Simmonds; Ricardo J José; Jamie Cheong; Shereen Boreland; et al. (BMJ Open Quality)
Aminoglycoside antibiotics cause ototoxicity for which baseline audiometric testing is recommended but often not done. Barriers to successful implementation include limited availability of sound-booths and audiologists. An ototoxicity monitoring programme (OMP) was implemented using tablet-based audiometry (TBA) by non-audiologists.A quality improvement project conducted over 1 year (19 April 2021 to 18 April 2022), using Plan Do Study Act (PDSA) cycles, monitored the adherence to the OMP using Shoebox Standard Edition application on iPads. Barriers to adoption were identified to determine potential solutions for improved adherence. Adult respiratory patients (cystic fibrosis (CF), bronchiectasis, non-tuberculosis mycobacteria (NTM) infection) aged 17–82 years receiving >1 day of intravenous aminoglycosides (IVAGs) at a single tertiary-referral hospital were included. Other reported outcomes were patient characteristics, risk factors associated with abnormal hearing and ototoxic shift.73 patients were tested in the OMP (46 received ≥2 hearing tests) giving an overall adherence rate of 69% after 12 months. Patient identification using referral and reporting systems initially improved adherence from 36% to 88% (p=0.03) during PDSA 1. Barriers to successful adherence were staff availability and COVID-19 infection outbreaks (p=0.057). Older age (p<0.001), higher Body Mass Index (p=0.041), non-CF bronchiectasis (p=0.01), non-CF NTM (p=0.028) and higher Hearing Handicap Inventory for Adults scores (p=0.002) were significantly associated with abnormal baseline hearing. 78% with hearing loss were asymptomatic. Ototoxic shift was associated with gentamicin use compared to amikacin/tobramycin (p=0.027). TBA was associated with high usability in patients ≤50 years old.TBA by non-audiologists was feasible and demonstrated good patient usability, permitting screening of patients within 72 hours of starting IVAG and earlier referrals for formal audiometry. Hearing loss and ototoxicity were detected at earlier stages, enabling more rapid decision-making and treatment modification.